Autism, early psychosis, and social anxiety disorder: understanding the role of social cognition and its relationship to disability in young adults with disorders characterized by social impairments - Pepper, K. L. (Transl Psychiatry, 2018)
Impairments in social cognition are believed contribute to disability, particularly for disorders characterized by difficulties in social interaction. There has been little transdiagnostic investigation of this across social cognition domains in young adults. A total of 199 young adults diagnosed with autism spectrum disorder (ASD; N = 53), early psychosis (EP; N = 51), and social anxiety disorder (SAD; N = 64) were compared against neurotypical controls (NT; N = 31) on a battery of lower and higher-order and self-report social cognition measures. For both ASD and EP, participants showed impaired performance on all lower-order emotion recognition tasks and one higher-order social cognition test. Self-reports of empathy were reduced in all clinical groups and particularly in ASD. For SAD, despite showing no objective social cognition impairment, self-reported empathy was reduced to the same level as EP. Discriminant analysis revealed that self-reported empathy and lower-order emotion recognition tests provide best capacity to differentiate groups. Regressions predicting disability revealed depression as the strongest predictor across all disability measures. Empathy provided additional predictive value for social disability and social interaction anxiety. Overall, results support a similar social-cognitive development profile across ASD and EP. While self-reported empathy differentiated between groups, discrepancy between objective social cognition test performance and self-reported empathy in the SAD group suggests probable threat-related self-monitoring report biases that likely further influence all group outcomes. As depression and empathy were the most important predictors of disability, regardless of diagnostic group, research is required to explore targeted interventions for difficulties in these domains to reduce disability.